Odpowiedzi

2010-03-25T18:51:26+01:00
A) 3(x- 1) -2 dla x=4,2
3x-3-2=3x-5
3*4,2-5= 12,6-5=7,6

b)2(y + 6) -4 (y-6) dla y= 1/2
2y+12-4= 2y+8
2*1/2+8=9

c) 3(a-8)-(5-2a) dla a= -0,5
3a-24-5+2a= 5a-29
5*(-0,5)-29= -31,5

d) 4(x-y)-(-x+y) dla x= 3/2, y= -1
4x-4y+x-y= 5x-5y
5*3/2-5*(-1)= 7,5+5= 12,5
2010-03-25T18:53:51+01:00
A)3(x- 1) -2 dla x=4,2
3x -3 = 3*4,2 -3 = 12,6 -3=9,6


b)2(y + 6) -4 (y-6) dla y= 1/2
2y +12 -4y +24 = -2y + 36 = -2*1/2 +36 =37

c) 3(a-8)-(5-2a) dla a= -o,5
3a -24 -5 +2a = 5a -29 = 5*-0,5 -29 = -2,5-29= -31,5

d) 4(x-y)-(-x+y) dla x= 3/2, y= -1
4x -4y +x -y = 5x -5y= 5*3/2 -5*-1 = 7,5 +5 = 12,5
2010-03-25T18:56:14+01:00
3x-3-2=3x-2
3*4,2-1=9,6

2y+12-4y+24=-2y+36
2*1/2+36=37

3a-24-5+2a=5a-29
5*0,5-292,5-29=-31,5

4x-4y+x-y=5x-5y
5*3/2-5*-1=7,5+5=12,5
1 5 1